Effect of Southern Chinch Bug on Weed Establishment in St. Augustinegrass - Curtis Rainbolt; Ronald Cherry; Russell Nagata (EDIS)
SS-AGR-277, a 3-page illustrated fact sheet by Curtis Rainbolt, Ronald Cherry and Russell Nagata, discusses the results of a study to further understand the relationship between southern chinch bugs and weeds in St. Augustinegrass in south Florida. Published by the UF Department of Agronomy, October 2007.